Linking IT Governance to Organizational Performance in Higher Education: The Role of Digital Capability and Organizational Agility - Amrullah Amrullah; Khairul Imtihan; Baiq Yulia Fitriyani; Mardi; Muhamad Rodi (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study examines how IT governance contributes to organizational performance through information systems (IS) success, digital capability, and organizational agility in higher education institutions. It addresses a critical gap by exploring why improvements in IT governance and system quality do not always translate into higher organizational capabilities and performance. A quantitative survey was conducted with 342 respondents from higher education institutions in Nusa Tenggara Barat (NTB), Indonesia, and analyzed using PLS-SEM. The results show that IT governance significantly improves system, information, and service quality. However, these dimensions do not significantly influence digital capability, and digital capability does not significantly affect organizational agility. Instead, organizational agility is the only construct that significantly enhances organizational performance, while IT governance shows no direct effect. These findings suggest that IT value creation is not linear but depends on the organization’s ability to translate technological resources into adaptive capabilities. This study provides empirical evidence on the indirect role of IT governance and offers a contextual clarification of IS success and digital capability relationships within NTB higher education institutions.